2002
DOI: 10.1177/001316402128775012
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Generalization: Moving Toward Improved Understanding and Use of Score Reliability

Abstract: Reliability generalization (RG) is a measurement meta-analytic method used to explore the variability in score reliability estimates and to characterize the possible sources of this variance. This article briefly summarizes some RG considerations. Included is a description of how reliability confidence intervals might be portrayed graphically. The article includes tabulations across various RG studies, including how frequently authors (a) report score reliabilities for their own data, (b) conduct reliability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 4 publications
2
65
1
1
Order By: Relevance
“…In particular, there is little data to evaluate the sensitivity of reliability coefficients to changes in task characteristics, respondents, and administration conditions. Vacha-Haase, Henson, and Caruso (2002) discuss a methodology for evaluating sensitivity of reliability coefficients, which they refer to as reliability generalization. Also a typology of task measures could be suggested that would link the kind of internal consistency reliability coefficients to the type of task.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there is little data to evaluate the sensitivity of reliability coefficients to changes in task characteristics, respondents, and administration conditions. Vacha-Haase, Henson, and Caruso (2002) discuss a methodology for evaluating sensitivity of reliability coefficients, which they refer to as reliability generalization. Also a typology of task measures could be suggested that would link the kind of internal consistency reliability coefficients to the type of task.…”
Section: Resultsmentioning
confidence: 99%
“…Reliability generalization also focuses on measurement error, an essential component of reliability, and sources for it, reliability generalization adds a way to understand the degree to which measurement error impacts the results (i.e. effect size) across studies (Vache‐Haase 1998, Vacha‐Haase et al. 2002).…”
Section: Aimsmentioning
confidence: 99%
“…Various measurement experts have reported on the problem of some researchers’ lack of reporting reliability coefficients for instruments used in their studies (Vache‐Haase 1998, Whittington 1998, Vacha‐Haase et al. 2002) as well as the importance of sample‐specific reliability estimates of scores for instruments (Nunnally & Bernstein 1994, Vache‐Haase 1998, Vacha‐Haase et al. 2002, Waltz et al.…”
Section: Aimsmentioning
confidence: 99%
“…In recognition of this, several journals have changed their editorial policies to require researchers to consider the reliability of data in hand when publishing results (e.g., Fan & Thompson, 2001). Although evidence suggests that researchers rely on reliability induction and fail to report the reliability of their data at an alarming rate (Vacha‐Haase, Henson, & Caruso, 2002), other evidence suggests gradual and steady improvement in reporting practices (Graham, Liu, & Jeziorski, 2006).…”
Section: Reliability Generalizationmentioning
confidence: 99%